Geloof as antwoord op versoening – ’n Pauliniese perspektief - Aarde, Andries van (Verbum et ecclesia, 2005)
The aim of this article is to critically assess Friedrich Nietzsche’s accusation of Paul that he replaced the "gentle gospel" of Jesus with an ideology of punishment, forgiveness, and reward. The article argues that the Pauline perspective on reconciliation has not the purport to satisfy either divine wrath or human needs - whether born from particularistic ethnocentrism or liberal globalism. Besides a siscussion of the expressions used by Paul to articulate his kerygma about redemption the article demonstrates that for Paul, faith functions as response to God’s act of reconciliation. God’s righteousness is the most prominent result of being reconciled. Faith as response to God’s salvation implies therefore that transformation and ethics are two sides of a responsive conduct which follows when God, as a gift, expiates the inequities of human beings.